Mikrobiologiczna synteza biologicznie aktywnych lipidów - Leman, Jacek (Komitet Biotechnologii PAN, 1993)
A significance of biologically active polyunsaturated fatty acids y-linolenic, arachidonic,dihomo-y-linolenic, eicosapentaenoic) in mammals and the reasons for their metabolic disturbances were reviewed. Fungi utilization in biosjmthesis of bio/medicallyactive fatty acids waspointed out and the presently used technologies as well as the forthcoming trends were shortlyannounced.
Keywords: biotechnologia